Serum γ-Glutamyltransferase and Risk of Metabolic Syndrome and Type 2 Diabetes in Middle-Aged Japanese Men - Noriyuki Nakanishi; Kenji Suzuki; Kozo Tatara (2004)
OBJECTIVE—To investigate the association between serum γ-glutamyltransferase (GGT) and risk of metabolic syndrome and type 2 diabetes in Japanese male office workers. RESEARCH DESIGN AND METHODS—This study included 2,957 metabolic syndrome-free men and 3,260 nondiabetic men aged 35–59 years who did not have medication for hepatitis, alanine aminotransferase (ALT) levels higher than three times the upper limit of the reference range, or a history of cardiovascular disease at study entry. Subjects were reexamined at periodic annual health examinations over a 7-year period. We used a modified National Cholesterol Education Program definition of metabolic syndrome with BMI instead of waist circumference and the revised criteria of the American Diabetes Association for type 2 diabetes. RESULTS—With adjustment for age, family history of diabetes, BMI, alcohol intake, cigarette smoking, regular physical activity (fasting plasma glucose for the risk of type 2 diabetes), and white blood cell (WBC) count, the risk of metabolic syndrome and type 2 diabetes increased in correlation with the levels of serum GGT, ALT, aspartate aminotransferase (AST), and alkaline phosphatase. Additional adjustment for all of the other liver enzymes attenuated these associations, but serum GGT remained a significant risk factor for the risk of both metabolic syndrome and type 2 diabetes (P for trend <0.001 for both). Top one-fifth versus bottom one-fifth relative risks of metabolic syndrome and type 2 diabetes were 2.23 (95% CI 1.51–3.30) and 2.44 (1.34–4.46), respectively. CONCLUSIONS—These results indicate that serum GGT may be an important predictor for developing metabolic syndrome and type 2 diabetes in middle-aged Japanese men.